If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -1) = 6x + 5 Reorder the terms: 3(-1 + 2x) = 6x + 5 (-1 * 3 + 2x * 3) = 6x + 5 (-3 + 6x) = 6x + 5 Reorder the terms: -3 + 6x = 5 + 6x Add '-6x' to each side of the equation. -3 + 6x + -6x = 5 + 6x + -6x Combine like terms: 6x + -6x = 0 -3 + 0 = 5 + 6x + -6x -3 = 5 + 6x + -6x Combine like terms: 6x + -6x = 0 -3 = 5 + 0 -3 = 5 Solving -3 = 5 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 55=15+1/2D | | 24-8x^2-x^4=0 | | 3(2x+1)=6x+5 | | 9p+3=6+8p | | 3/7(1+6x)=1 | | 32-3x=20 | | 12x+1=2(6x+3) | | y=2(-1)+1 | | (1)-y=6 | | 3x+39=6x+13 | | 5(2X+8)=5 | | (-1)-y=6 | | 4x+65-2x=4x+(-40)+13-3x | | -13-5=14-8x | | -3(4x-2)=30 | | 3m+2=4m-6 | | 9+1/2x=5x-1 | | 17a-8(a+1)=3(a-3) | | 1/x=98.78 | | -x+14=7+x | | 3(x+4)=5-(x-11) | | 6x+5=8+6x | | 6-q=4-2q | | 5r-2=-r+4 | | -2.3c=11.5 | | 2x+7=11-7x | | -12x=3 | | 7x+11=11x+12 | | 50x^2+200=0 | | 3x-12/6+x/30=x/5-1 | | 12x+18=2(6x+3) | | 9x=8(3x+5) |